(untitled) (Research, Society and Development, 2025)
Venous thromboembolism (VTE) is the third leading cause of vascular mortality worldwide and is considered the main cause of preventable deaths in hospitalized patients. The present study aims to identify the main etiologies and risk factors associated with cases of venous thromboembolism (VTE) treated at the Medical Specialties Clinic of UNIFAL-MG, in Alfenas – MG. This is a retrospective observational study based on the review of medical records of patients diagnosed with VTE who were treated at the hematology clinic of UNIFAL between January 2018 and July 2024. Demographic data, risk factors, clinical progression, and treatment were collected. Patients were divided into two groups: Group 1 and Group 2, according to clinical history. Group 1 had a mean age of 31.7 years, with a notable prevalence of family history. Group 2, with a mean age of 41.2 years, showed a higher prevalence of obesity and oral contraceptive use. The main thrombotic sites were the lower limbs, with frequent progression to pulmonary embolism. Etiological stratification revealed distinct clinical profiles, reinforcing the importance of individualized approaches to the prevention and treatment of VTE. Limitations such as the absence of complementary tests and loss to follow-up were observed, but the data contribute to the local epidemiological understanding and the improvement of clinical practices.